2015
DOI: 10.1002/mrm.25877
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and reproducibility of whole brain myelin water mapping in 4 minutes using fast acquisition with spiral trajectory and adiabatic T2prep (FAST-T2) at 3T

Abstract: Purpose To develop and measure the reproducibility of 4-min whole brain myelin water fraction (MWF) mapping using fast acquisition with spiral trajectory and T2prep (FAST-T2) sequence at 3T. Methods Experiments were performed on phantoms, 13 volunteers, and 16 patients with multiple sclerosis. MWF maps were extracted using a spatially constrained non-linear algorithm. The proposed adiabatic modified BIR-4 (mBIR-4) T2prep was compared with the conventional composite T2prep (COMP). The effect of reducing the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 42 publications
1
97
1
Order By: Relevance
“…MWF maps were reconstructed from FAST-T2 data using a multi-voxel nonlinear least-squares data-fitting algorithm with spatial smoothness constraints. 25 The lower and upper T2 bounds for each of the three water pools (in milliseconds) were set to [5 20], [20 200], and [200 2000], respectively (corresponding to myelin water, intra/extra-cellular water, and long-T2 water such as CSF). MWF was calculated as the ratio of the myelin water signal and the total water signal within a voxel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MWF maps were reconstructed from FAST-T2 data using a multi-voxel nonlinear least-squares data-fitting algorithm with spatial smoothness constraints. 25 The lower and upper T2 bounds for each of the three water pools (in milliseconds) were set to [5 20], [20 200], and [200 2000], respectively (corresponding to myelin water, intra/extra-cellular water, and long-T2 water such as CSF). MWF was calculated as the ratio of the myelin water signal and the total water signal within a voxel.…”
Section: Methodsmentioning
confidence: 99%
“…This study aimed to address these challenges by combining two recently developed techniques, myelin water fraction (MWF) imaging using fast acquisition with spiral trajectory and T2prep (FAST-T2) 24, 25 and QSM with automatic uniform CSF zero reference (QSM0). MWF is a well-validated quantitative MRI biomarker for myelin, 26, 27 which can be mapped efficiently and reproducibly with FAST-T2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have already focused on fast acquisition of multiecho data for the purpose of MWF mapping. For instance, Prasloski et al showed that whole brain MWF mapping was possible under 15 min using a gradient‐spin echo sequence with 32 TEs, whereas Nguyen et al showed that even faster whole brain MWF mapping was possible acquiring 6 TEs in 4 min using a modified T 2 prep sequence . In this study, we already showed the applicability of the OMP algorithm for multiecho data acquired using a 3D GRASE sequences.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated in-vivo MCR in the human brain for myelin mapping using MRI (21). Since then, MCR has become an active area of research, with several methods having been developed to either accelerate data acquisition (23, 28, 29, 32, 36, 37, 39, 40, 55) or to improve parameter determination (23, 25, 36, 44, 5665). Among these, mcDESPOT permits rapid whole-brain coverage, and so may have particular potential for clinical investigations, especially those involving patients with limited ability to remain stationary for the lengthy duration of MRI studies.…”
Section: Discussionmentioning
confidence: 99%